A dictionary of construction, surveying, and civil engineering - Gorse, Christopher A.; Johnston, David, 1950-; Pritchard, Martin (Civil engineer) (Oxford quick reference., 2020)
In over 8000 entries, this dictionary covers the key areas of construction and civil engineering, construction technology and practice, construction management techniques and processes, as well as legal aspects such as contracts and procurement.--